Extraction of a deeply impacted lower third molar by sagittal split osteotomy - VAROL, ALTAN (Mosby Inc., 2009)
Extraction of deeply impacted wisdom molars from the lower jaw with the bone osteotomy may necessitate removal of extra bone and complicate the procedure with damage to the inferior alveolar nerve and iatrogenic fractures of the mandible. In such cases, the sagittal split osteotomy offers excellent exposure to the operative field and minimizes bone loss at the mandibular ramus. The presented case includes removal of a deeply impacted lower third molar presenting mild infection from the mid-ramus using the sagittal split of the mandible. The sagittal split osteotomy, which appears to be a reliable technique, should be the method of preference when lower molars are deeply positioned between buccal and lingual cortices. © 2009 Mosby, Inc. All rights reserved.